Legal analysis of the Malaysian Animals Act 1953 (revised 2006) in regard to animal testing: with special reference to the legal position in the United Kingdom / Afiqah Najiha Mahadi … [et al.] - Mahadi, Afiqah Najiha; Roszamman, Nur Anees Syafwah; Hassan, Farah Syahirah; Azmi, Nik Zahira (2014)
This research attempts to analyze the adequacy of the present legislation, Animals Act 1953 (Revised 2006) in addressing the animals rights with regards to animal testing. On top of that, the Animals (Scientific Procedures) Act 1986 implemented in the United Kingdom will be examined and compared with the Malaysian Animals Act 1953 (Revised 2006). The reason behind United Kingdom being chosen as a comparison is because the country imposes a stricter law on industries and scientists who use animals as their experimentation object. Comparison between these two countries is also made so that it will give a clearer view that Malaysia is still lacking in regulations when it comes to animal testing despite the existence of the Animals Act 1953 (Revised 2006). In operating this research, an analytical and critical study will be conducted using a qualitative method whereby the data will be accumulated through doctrinal and empirical methods. Therefore, this research targets to urge the policy makers to pass the Animal Welfare Bill as well as having standardized regulations, guidelines and procedures to safeguard animals' rights and welfare in filling our lacunae in the existing law. The researchers have addressed the weaknesses in this research by providing the solutions that can be done in order to strengthen the integrity of enforcement and suggested a few amendments to make the animals law become more effective in Malaysia.